Role of Technology Integration in the Development of 21st-Century Skills STEM University in Zimbabwe - Doris Chasokela (Scientia Publica Media, 2025)
Technology use is crucial and fundamentally alters how universities teach and learn in the twenty-first century. The influx of various technologies supports the development of three key 21st-century skills: life and career skills, learning and innovation skills, and information, media, and technology skills. Social constructivism theory serves as the study’s theoretical foundation, emphasizing the importance of collaborative learning environments where students construct knowledge through social interaction. A case study design and a qualitative methodology were employed in the investigation to gain deep insights into the experiences of participants. Those involved in the study included STEM lecturers, faculty technicians, and both first- and final-year undergraduate students; they were chosen using a purposeful sampling procedure to ensure a rich variety of perspectives. Data were collected through in-depth interviews, which provided valuable qualitative insights. The paper explores the 21st-century skills essential for STEM learning, focusing on the implications, competencies, and perceptions of various stakeholders. The study established a pressing need for training in technology integration among faculty. Additionally, there was minimal support from administration and technicians, as well as a lack of adequate resources. Participants expressed the need for ample time to prepare for lessons, highlighting the challenges educators face. Consequently, it is recommended that the implementation of technologies should begin with strong support from administrators and technicians in sourcing necessary resources. Lecturers play a crucial role in preparing students for the modern workplace, and they require continuous training and support from technicians. Furthermore, administrators should foster collaboration with other STEM-offering universities to stay current with rapidly evolving technologies, ensuring a comprehensive approach to education in the digital age. This collaboration can significantly enhance the educational quality and effectiveness of STEM programs.